ADAPTASI KURIKULUM DAN METODE PEMBELAJARAN PENDIDIKAN ISLAM DALAM ERA DIGITAL - Risma Dongoran; Ayu Hasanah Pohan; Nurlida Asni; Noorhani Dyani Laksmi (Ahsani Taqwim: Jurnal Pendidikan dan Keguruan, 2026)
The transformation of Islamic education is a response to the dynamics of the times that continue to develop, both in terms of social, technological, and globalization. Islamic education, which was initially oriented towards the formation of morals and mastery of religious knowledge, is now required to integrate spiritual values ​​with contemporary knowledge. This transformation process includes changes in curriculum, learning methods, and the use of technology in teaching and learning activities. Islamic education is no longer only focused on madrasahs and Islamic boarding schools, but also reaches more modern formal institutions that are accredited nationally and internationally. The challenge faced in this process is how to maintain Islamic values ​​so that they remain the main foundation, while accommodating the need for global competence. Therefore, the transformation of Islamic education must be carried out holistically and continuously, involving all elements: government, educational institutions, teachers, parents, and the community. Strengthening character, digital literacy, and 21st century skills are important parts of this reform. Thus, Islamic education is able to produce a generation of Muslims who are not only religious, but also capable, critical, and productive in global life. This transformation is a strategic step to make Islamic education relevant and highly competitive amidst changing times.